The relationship between the servant leadership and employee performance in the organization / Fatin Nur Mahirah Azeri - Azeri, Fatin Nur Mahirah (Faculty of Business and Management, 2019)
The final report project was carried out in order to fulfill the requirement of the Academic Project (ASM60l). The study was conducted at the government organizations at Pahang. There are two main objectives were to identify employees performance level in the organization and to identify the relationship between servant leadership and employee performance in the organization. By referring to Krejcie and Morgan table (1970), the scopes were focused on the certain number of population. The sample sizes had been taken referred to the sample size for a given population. The sampling technique used is simple random sampling. The data will be analyzed and interpreted using SPSS software. It is hope that from the overall findings, we could discover that employees at UiTM Cawangan Pahang, Kampus Jengka to had a servant leader at office. The employees are able to know more about the elements of servant leadership which are agape love, services, trust and humility. It was hope that the more significant it is toward handling the issues among them.